2010
DOI: 10.1371/journal.ppat.1000818
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin Phosphorylation by v-Cyclin-CDK6 Controls KSHV Latency

Abstract: Nucleophosmin (NPM) is a multifunctional nuclear phosphoprotein and a histone chaperone implicated in chromatin organization and transcription control. Oncogenic Kaposi's sarcoma herpesvirus (KSHV) is the etiological agent of Kaposi's sarcoma, primary effusion lymphoma (PEL) and multicentric Castleman disease (MCD). In the infected host cell KSHV displays two modes of infection, the latency and productive viral replication phases, involving extensive viral DNA replication and gene expression. A sustained balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 56 publications
(65 reference statements)
2
48
0
1
Order By: Relevance
“…These studies suggested that KSHV can maintain its latency through regulation of the levels and activities of HATs and HDACs. Phosphorylation of the cellular protein nucleophosmin can control KSHV latency (89). The results obtained in our study also showed that a LANA and AK-B complex can enhance phosphorylation of survivin during KSHV latent replication (89).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These studies suggested that KSHV can maintain its latency through regulation of the levels and activities of HATs and HDACs. Phosphorylation of the cellular protein nucleophosmin can control KSHV latency (89). The results obtained in our study also showed that a LANA and AK-B complex can enhance phosphorylation of survivin during KSHV latent replication (89).…”
Section: Discussionsupporting
confidence: 71%
“…Phosphorylation of the cellular protein nucleophosmin can control KSHV latency (89). The results obtained in our study also showed that a LANA and AK-B complex can enhance phosphorylation of survivin during KSHV latent replication (89). Therefore, the stabilization and activation of survivin can create an environment for hyperacetylation of histones in KSHV latently infected cells.…”
Section: Discussionsupporting
confidence: 62%
“…In particular, H3K27 methyltransferase (EZH2) activity, depletion of which reactivates KSHV (20,22), has been shown to require HDACs (48). Also, the viral protein LANA inhibits reactivation and forms multiprotein complexes with HDAC1 (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleophosmin (NPM), a multifunctional nuclear phosphoprotein and a histone chaperone implicated in chromatin organization and transcription control, has been reported to be a novel link between LANA/vCyclin and KSHV latency. NPM phosphorylation by the vCyclin-cyclindependent kinase 6 complex supports its interaction with LANA and enables the transcriptional silencing of the KSHV lytic genes needed for latency (96). Interestingly, NPM phosphorylation has been shown to be regulated by lipoxygenases (97).…”
Section: Discussionmentioning
confidence: 99%